Análise da aplicação de ferramenta computacional de modelagem e simulação humana no projeto de situações produtivas - Moura, Daniel Braatz Antunes de Almeida (2009)
This research aims at presenting the human modeling and simulation contextualized by Ergonomic Work Analysis (EWA) and Probable Future Activities to assist in the design of new workstations. Two case studies in which human simulation was applied using the software Jack were analyzed. The first case study concerns the design of a new attendance counter in a Governmental Postal Company. The second concerns the design of a workstation in the production line of surgical needles in an industry of hygiene and medical products. The results indicate the contributions and challenges of using such technology in projects aiming envisaging issues of health and productivity. The use of simulation together with the Ergonomic Work Analysis (EWA) enabled predicting probable future activities and the participation and integration of actors involved in these social process.